Increasing Parents' Knowledge About the Needs of Families with Children with Special Needs Using Health Counseling Methods - Elis Noviati; Ima Sukmawati; Rudi Kurniawan; Dena Mustika Ningrum; Fidya Anisa Firdaus (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Children with disabilities are not able to carry out activities independently so they will have a greater dependence on their families. Families or parents are the main service providers for children with disabilities in terms of growth and development and independence of children with disabilities. Based on this, it shows that the family is an important component in achieving the needs of children with disabilities. Empowerment of families is very important to improve the quality of family parenting in caring for children with disabilities. This community service aims to improve the quality of parenting for families with children with disabilities. Partners in this service activity are families with children with disabilities at the Ciamis Special School. The service methods that will be carried out include blood pressure checks, lectures, discussions and questions and answers. Community service went smoothly all participants were committed to implementing all the recommendations given by the resource persons